The Brief Fatigue Inventory is reliable and valid for the burn patient cohort. Issue 5 (August 2015) - Toh, Christopher; Li, Marie; Finlay, Vidya; Jackson, Teresa; Burrows, Sally; Wood, Fiona M.; Edgar, Dale W.
Highlights Large cohort study to determine a measure of fatigue levels after burn. Brief Fatigue Index is a reliable and valid measure of fatigue in burn patients. Fatigue levels are greater in major burns and in females.